2017
DOI: 10.1007/s00267-016-0816-x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint assessment of Western Australian Groundwater Recycling Scheme

Abstract: This research has determined the carbon footprint or the carbon dioxide equivalent (CO eq) of potable water production from a groundwater recycling scheme, consisting of the Beenyup wastewater treatment plant, the Beenyup groundwater replenishment trial plant and the Wanneroo groundwater treatment plant in Western Australia, using a life cycle assessment approach. It was found that the scheme produces 1300 tonnes of CO eq per gigalitre (GL) of water produced, which is 933 tonnes of CO eq higher than the desali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In general, the results of the study confi rm the fi ndings in different studies that showed the biggest share of electricity and chemicals as far as environmental impact in disinfection process is concerned (Raghuvanshi et al 2017, Simms et al 2017. As opposed to this, while environmental impacts are concerned, the substances persisting in water after the process have very little impact on environment.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In general, the results of the study confi rm the fi ndings in different studies that showed the biggest share of electricity and chemicals as far as environmental impact in disinfection process is concerned (Raghuvanshi et al 2017, Simms et al 2017. As opposed to this, while environmental impacts are concerned, the substances persisting in water after the process have very little impact on environment.…”
Section: Discussionsupporting
confidence: 75%
“…Simms et al take similar approach to the assessment of water recycling schemes that are introduced in Western Australia. The difference is related to the disinfection process that in this case is not solely chlorination but a combined process of UV disinfection and fl uoride and chlorine additives at the fi nal stage (Simms et al 2017). Both of the studies agree on the major impact factor in water treatment plant that is electricity used and both show that the chemicals used in the treatment process are the second biggest impact factor (Raghuvanshi et al 2017, Simms et al 2017.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…At present, the Perth scheme exceeds the carbon footprint of the city's desalination plants, which are powered by renewable energy . 41 At time of writing, the state government is building a renewable energy generator to supply the needs of an expanded wastewater recycling scheme. 42 Perth's water flourishing, therefore, is dependent on reconciling the tensions between energy, ecology, and consumption.…”
Section: Groundwater Replenishment In Perth Western Australiamentioning
confidence: 99%